THE EFFECT OF WORK ENVIRONMENT, PROFESSIONAL TRAINING, AND SELF-EFFICACY ON STUDENTS’ INTENTION TO PURSUE A CAREER AS PUBLIC ACCOUNTANTS(An Empirical Study on Undergraduate Accounting Students at Universitas Udayana) - Nesia Yoseva Putri Sihotang; I Ketut Suryanawa (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The profession of public accountants plays a vital role in supporting the economic transformation and development of a country. However, the proportion of accounting graduates who pursue careers as public accountants in Indonesia remains relatively low. This study aims to examine the influence of work environment, professional training, and self-efficacy on students’ intention to pursue a career as a public accountant. The population in this study consisted of 890 undergraduate accounting students at Udayana University, with a sample size of 574 students. Data were collected using a survey method through non-probability purposive sampling. The data analysis employed a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). The results of the analysis reveal that the work environment, professional training, and self-efficacy have a positive influence on students’ intention to pursue a career as public accountants.